Development and Validation of UV Spectroscopic Method for Estimation of Propranolol in Bulk and Tablet Dosage Form - Sowjanya, Gundeboina; Ahmed, Rezwan; Sanaha, Mohammad; Naresh, Yelgaboina; Raja, Badavathu; Chary, Vemuluri Padmabhushana; Chinnaeswaraiah, Maram (Asian Journal of Biological and Life Sciences)
Background: Propranolol is a widely used non-selective beta-blocker prescribed for hypertension, arrhythmias, and anxiety -related conditions. Simple, robust, and cost-effective analytical methods are essential for its routine quality control in pharmaceutical formulations. Materials and Methods: A UV Spectroscopic method was developed and validated in accordance with ICH Q2 (R1) guidelines for the estimation of Propranolol. The method was validated for parameters including linearity, accuracy, precision, robustness, ruggedness, Limit of Detection (LOD), Limit of Quantification (LOQ), Assay and solution stability. The absorbance was measured using a suitable wavelength and standard and test solutions were prepared accordingly. Results: The method showed linearity in the concentration range of 1-8 µg/mL with a correlation coefficient (R2) of 0.999. Accuracy was within the acceptable range, with recovery values between 97.34% and 100.1%. Precision studies yielded % RSD values of less than 2%, indicating good repeatability and intermediate precision. This method was robust and rugged under small deliberate variations. The LOD and LOQ were found to be below 1 µg/mL, confirming high sensitivity. The assay result was 100.62% and the standard stock solution was stable for 24 hr at room temperature. Conclusion: The validated UV Spectroscopic method is simple, accurate, precise, and cost-effective. It is suitable for routine analysis and quality control of Propranolol in bulk drug and pharmaceutical dosage forms.
Keywords: Propranolol; UV Spectroscopy; Method validation; ICH guidelines; Stability.